Improving The Properties Of Fresh & Hardened Concrete By Using High Range Water Reducing Admixtures (Super Plasticizers) - Taher, Rabah Basheer Mohammed (Al-Mukhtar Journal of Sciences, 2009)
This paper studies the ability of improving the properties of the concrete by using a super plasticizer in a powder form. In the practical part of this study (16) different mixes were carried out. The first mix was made without using the super plasticizer in order to use it as a reference to compare its properties with the properties of the other (15) mixes, to that we added the super plasticizer. In these mixes different weights of cement, water: cement ratios and different ratios of the super plasticizer were used. For each mix a slump test of fresh concrete was carried out and (6) cubes were made to test their compressive strength at the age of (7) & (28) days. After comparing the properties of the (15) mixes with the properties of the reference mix it has been found that the adopted super plasticizer can be used to accomplish these four aims: 1- Increasing the workability of fresh concrete without decreasing the compressive strength of the hardened concrete. 2- Increasing the compressive strength of the hardened concrete without decreasing the workability of fresh concrete. 3- Decreasing the permeability of concrete by reducing the water: cement ratio and increasing its compression strength. 4- Decreasing the weight of cement in the mix without decreasing the compressive strength of the hardened concrete and the workability of the fresh concrete. According to these conclusions the following recommendation can be drawn: 1- Using the super plasticizers in concrete mixes, that are used in narrow sections or in sections of a heavy reinforcement. 2- Using the super plasticizer in concrete mixes which should possess a high compressive strength and an appropriate workability. 3- Using the super plasticizers in producing concrete mixes, that are exposed to severe conditions such as shallow and deep foundations, concrete exposed to seawater and chemicals. 4- Using the super plasticizer to reduce the weight of cement without reducing the compressive strength & workability of the concrete.